Variation of irrigation water quality in microregion Catolé do Rocha, PB, Brazil - Costa, Rubens Germano; Gheyi, Hans Raj (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this research was to study the water quality variations in the municipalities of the microregion CatoIé do Rocha, PB, Brazil. One hundred and sixty water samples were collected at two occasions: the first in November 1980 (dry season); and the second in May 1981 (just after the rainy season). These samples were analysed and classified as to risks of salinity, sodicity, residual sodium carbonate and boron. The results showed that after the rains there was an increase of about 7,6% in the good quality water for irrigation (C1S1 and C2S1), and in 8% of the water samples the boron level was above 1.25 ppm. According to these results, it may be concluded that the irrigation water commonly found has good quality (CE < 750 µmhos/cm), and can be used for irrigation of the majority of soils and crops, with little probability of salinity and/or sodicity risks.